Parametric design and its role in designing building facades (An analytical study) (Al-Academy, 2024)
Parametric design is the primary means of creating designs that have a free and modern character that is compatible with current architecture and what it seeks to achieve in terms of ventilation and natural lighting in buildings, in addition to its potential in creating many ideas. Therefore, the current study aims to reveal the role of parametric design in designing buildings’ facades. The study followed the descriptive analytical approach for (3) building facades that were selected as a purposive sample according to specific criteria. The study revealed the following findings: The compatibility of parametric design with nature has led to the existence of architectural facades that touch society intellectually and culturally. It also showed that the triangular grid of the parametric design helps the wind pass through and make the building more efficient. The study recommends conducting more studies focusing on parametric design because of its multiple and diverse design constructs. In addition, encouraging designers to use parametric design in designing building facades to solve design problems related to the building’s function.